Hambatan Penegakan Hukum Terhadap Praktik Tukang Gigi Tanpa Izin di Kabupaten Batang - Hasna Azahrani Maulidina; Sulistyanta Sulistyanta (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
This legal writing aims to examine the obstacles to law enforcement against dentists who practice without a license in Batang Regency, Central Java. This research uses empirical legal research methods or non doctrinal research. Based on the results of the study, it is known that the obstacles found are the absence of regional regulations governing the licensing of dental practices.